Macroscopic thermal diode with stable rectification ratio by thermal null medium. (January 2023) - Dai, Hongtao; Sun, Fei; Chen, Hanchuan; Liu, Yichao; Yang, Yibiao; Chen, Zhihui; Liang, Shaowei; Wang, Zheng
Abstract: Thermal diode can achieve a unidirectional and irreversible thermal transport, which can be used for direction-selective thermal management. Here we demonstrate a macroscopic thermal diode by asymmetrically embedding staggered structure of copper and expanded polystyrene sheets in stainless steel background, which can achieve a stable high thermal rectification ratio at room temperature. For the fabricated samples measured here, we observe a nearly constant thermal rectification ratio ∼1.6 at room temperature, when the temperature bias applied on both sides changes from 25 K to 50 K or the input heat power changes from 10 W to 15 W. In contrast to the conventional methods, this approach provides a new way to design macroscopic thermal diode with a stable thermal rectification effect at room temperature, which opens up new possibilities for macroscopic heat preservation, energy-saving buildings, and direction-selective thermal camouflages.